Tourism, creative industries, and (youth) subcultures in the UK - Adams, Ruth (Diálogo com a Economia Criativa, 2018)
If we consider the aspects of British culture that might be expected to appeal most to tourists, what are the first things to come to mind? Conventionally it has been attractions such as ancient castles and pretty old cottages, beautiful coastlines and countryside, the Royal Family and ‘British tea time’. Many tourists also visit the museums, galleries and theatres of London and other big cities. Popular culture is also a driver for tourism in the UK, and is attracting fans of movies and television shows such as Harry Potter, Game of Thrones and Doctor Who, keen to visit filming locations and theme parks. Some tourists wish to connect with the history of Britain’s music and youth (sub)cultures, and can explore, for example, the legacies of the Beatles and the ‘Swinging Sixties’, or the sights and sounds of punk rock. Visitors from overseas can also immerse themselves in the UK’s contemporary art, music and fashion cultures - at festivals and nightclubs, in shops and markets, and on ‘street culture’ tours - and these types of experience are growing in importance and prominence in Britain’s tourism economy. This article, then, will examine the evolving relationship between tourism, the creative industries, and youth/subcultures in the UK, and consider some of the arguments and issues arising from it, such as the extent to which this might be considered a positive and sustainable development.